Influence of atmospheric trace elements wet deposition on soils and vegetation of Qilian Mountain forests, China. (August 2022) - Zang, Fei; Chang, Yapeng; Zhao, Xinning; Wang, Hong; Zhao, Chuanyan; Nan, Zhongren; Wang, Shengli; Wu, Yi
Graphical abstract: Highlights: Concentrations of Cu in rainwater and Zn in particulate were the highest among TEs. Forest soils had higher Pb, Ni concentrations and lower Cd, Hg concentrations. The Zn, Ni, Pb, and Cu have accumulated in forest vegetation and tissues. Abstract: The biogeochemical cycling of trace elements (TEs) in forest ecosystems is important because it plays a role in providing essential nutrients to plants and soils and because it can potentially have toxic effects. In this study, we investigated the concentration of TEs in atmospheric wet deposition, vegetation and soil in Qinghai spruce (QS) and Qilian juniper (QJ) forests of the Qilian Mountains. Our results show that the average concentrations of Cu in rainwater in QS and QJ forests were 10.30 and 5.35 μg L −1, respectively, the highest concentrations of all TEs in these environments. We suggest that the particulate matter present in the air was the main contributor of TEs in atmospheric wet deposition, which is affected by element specificity, regional factors, and the scavenging process during rainfall events. Most vegetation and tissues had high concentrations of Zn, Ni, Pb, and Cu, suggesting that these elements have accumulated in plants. The Zn, Pb, and Ni levels in forest plants may be correlated with those in forest soils. Our study highlights the role that atmospheric wet deposition can play in affecting TEs cycling across forest ecosystems. Managers need to further reduce TEs levels in emissions from surrounding sources and improve long-term observation of TEs in forest ecosystems.